Ambient Particulate Matter with Blood Pressure in Adult Women Living in Urban City - Aliyyah, Nurusysyarifah; Kusnoputranto, Haryoto; Wispriyono, Bambang; Fitria, Laila (UI Scholars Hub, 2024)
Ambient air pollution, especially from fine particles, contributes to human mortality from cardiovascular and respiratory diseases, for which high blood pressure (BP) is a major modifiable risk factor. This study aimed to analyze the influence of ambient particulate matter (PM2.5) on the risk of high BP leading to hypertension. This study used a cross-sectional design on 118 adult women living in Central Jakarta, Indonesia. Participants were selected from a 1-km radius of the nearest air quality monitoring station with available data PM2.5. Linear regression was analyzed to examine the relationship between PM2.5 and systolic and diastolic BPs adjusted for potential confounders. The annual means of PM2.5 concentration was 36±5.74 μg/m3. The linear regression model showed that PM2.5 exposure was associated with systolic BP after controlling with age and body mass index (r = 0.408; R2 = 0.167). The second model showed that exposure to PM2.5 concentration could explain about 10.9% variation of diastolic BP after controlling with age, length of stay, body mass index, smoking status, and diabetes mellitus record. Ambient air PM2.5 has a risk of BP and hypertension among adult women in Central Jakarta.